2018
DOI: 10.1007/s12178-018-9527-7
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Recommendations for Use of Platelet-Rich Plasma

Abstract: Purpose of Review This review evaluates current clinical literature on the use of platelet-rich plasma (PRP), including leukocyterich PRP (LR-PRP) and leukocyte-poor PRP (LP-PRP), in order to develop evidence-based recommendations for various musculoskeletal indications. Recent Findings Abundant high-quality evidence supports the use of LR-PRP injection for lateral epicondylitis and LP-PRP for osteoarthritis of the knee. Moderate high-quality evidence supports the use of LR-PRP injection for patellar tendinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
161
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(222 citation statements)
references
References 106 publications
(77 reference statements)
2
161
0
15
Order By: Relevance
“…In another randomized controlled trial, treatment of patients with chronic lateral epicondylitis with PRP reduced pain and increased function significantly, exceeding the effect of corticosteroid injection even after a follow-up of 2 years (21) . There is high-quality evidence supports the use of leucocyte poor-PRP injections for osteoarthritis of the knee (17) . However, the clinical application of PRP in hip arthritis, rotator cuff tendinopathy, bone repair and high ankle sprains remains controversial with insufficient evidence (7,17) .…”
Section: Orthopedicsmentioning
confidence: 97%
See 2 more Smart Citations
“…In another randomized controlled trial, treatment of patients with chronic lateral epicondylitis with PRP reduced pain and increased function significantly, exceeding the effect of corticosteroid injection even after a follow-up of 2 years (21) . There is high-quality evidence supports the use of leucocyte poor-PRP injections for osteoarthritis of the knee (17) . However, the clinical application of PRP in hip arthritis, rotator cuff tendinopathy, bone repair and high ankle sprains remains controversial with insufficient evidence (7,17) .…”
Section: Orthopedicsmentioning
confidence: 97%
“…There is high-quality evidence supports the use of leucocyte poor-PRP injections for osteoarthritis of the knee (17) . However, the clinical application of PRP in hip arthritis, rotator cuff tendinopathy, bone repair and high ankle sprains remains controversial with insufficient evidence (7,17) . On the other hand, many randomized trials found no effect of PRP on Achilles tendinopathies (22)(23)(24) .…”
Section: Orthopedicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Tennis Elbow [35] Hamstring [68] Knee [47] Extensor digitorum longus [50] Ankle [27] Gastrocnemius [56] Carpal Tunnel [65] Rotator Cuff [54] Tibialis Anterior [21] [52] ▶Fig. 1 Illustration shows clinical and pre-clinical evidence for the beneficial effects of platelet-based applications on different areas of the body for tendon, ligament and skeletal muscle regeneration.…”
Section: Recent Evidence For Platelet-based Applications To Remodel Smentioning
confidence: 99%
“…This microenvironment may be potentially harmful in already existing cancers; however, platelet-based applications are argued to be autologous and non-harmful as they do not induce mutagenesis [64]. On the other hand, clinical trials report an effective and safe outcome to using platelet-based applications for multiple treatments with no observed side effects [15,17,41,50,65]. Additionally, allogeneic platelet-rich plasma has recently been deemed safe for osteoarthritis patients according to a human pilot study [66].…”
Section: Safety Of Platelet-based Applications For Use By Athletesmentioning
confidence: 99%